2016
DOI: 10.1007/s00405-016-4044-z
|View full text |Cite
|
Sign up to set email alerts
|

Children with chronic lung diseases have cognitive dysfunction as assessed by event-related potential (auditory P300) and Stanford–Binet IQ (SB-IV) test

Abstract: Chronic lung disease (CLD) in children represents a heterogeneous group of many clinico-pathological entities with risk of adverse impact of chronic or intermittent hypoxia. So far, few researchers have investigated the cognitive function in these children, and the role of auditory P300 in the assessment of their cognitive function has not been investigated yet. This study was designed to assess the cognitive functions among schoolchildren with different chronic pulmonary diseases using both auditory P300 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The underlying mechanisms of cognitive impairments in COPD remain a controversial issue. Hypoxemia, hypercapnia, or vascular comorbidities have been proposed as possible causes of brain alterations in patients with COPD 34,35. Ortapamuk and Naldoken4 reported that individuals with severe COPD may develop changes in brain perfusion due to hypoxemia, leading to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of cognitive impairments in COPD remain a controversial issue. Hypoxemia, hypercapnia, or vascular comorbidities have been proposed as possible causes of brain alterations in patients with COPD 34,35. Ortapamuk and Naldoken4 reported that individuals with severe COPD may develop changes in brain perfusion due to hypoxemia, leading to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of the study was to analyze and compare attention and memory performance in pediatric patients with cystic fibrosis (CF), inflammatory bowel disease (IBD) and in healthy controls. 28 patients with CF, 30 patients with IBD and 30 healthy subjects took part in the study (all in age range of [7][8][9][10][11][12][13][14][15][16][17]. All subjects were in intellectual norm.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Cognitive impairments have also been found in chronically ill children and adolescents. [8][9][10][11] Cognitive dysfunction in chronic illnesses may be subtle and difficult to find, and the underlying mechanisms are yet to be fully determined. There are several hypotheses that have been proposed to explain cognitive deficits in chronically ill patients including: the impact of depression and anxiety that often occur in chronic illnesses, negative side effects of medication used in the treatment, and the disease process itself that may lead to neuropsychological impairments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations